2015
DOI: 10.1039/c4ra16957c
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical coated metal hydroxide nanoconstructs as potential controlled release carriers of photosensitizer for skin melanoma

Abstract: Inorganic nanostructured ensembles containing an anionic clay matrix with layered double hydroxide (LDH) were designed in nanooncology for photosensitizer delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 106 publications
0
35
0
Order By: Relevance
“…Extensive studies have shown that HT can form intercalated structures with different types of anions, such as inorganic anions, complex anions, anionic polymers, drugs, and organic biochemical anions such as amino acids and nucleic acids. 13,16,[18][19][20] These interactions occur by an anion exchange mechanism in which the anions residing in the interlayer space are replaced by the aforementioned anions. 21 This intercalation allows for the protection of drugs/biomolecules from degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have shown that HT can form intercalated structures with different types of anions, such as inorganic anions, complex anions, anionic polymers, drugs, and organic biochemical anions such as amino acids and nucleic acids. 13,16,[18][19][20] These interactions occur by an anion exchange mechanism in which the anions residing in the interlayer space are replaced by the aforementioned anions. 21 This intercalation allows for the protection of drugs/biomolecules from degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The unique ion-layer charge interaction in the supermolecular structure allow for the intercalation of various anionic molecules and fluorescent dyes via ion-exchange to construct a variety of LDH nanohybrids that have desirable properties for various uses, such as drug delivery [32][33][34][35][36], vaccination [37], targeting [38], and imaging [39,40]. LDHs have been used as a carrier for various negatively charged bio-moieties, for instance siRNA [31,[41][42][43][44][45][46], antibodies [2], carbohydrates [47], amino acids [48], enzymes [49], antimicrobial drugs [50,51], anti-inflammatory drugs [52], and anticancer drugs [33,36,[53][54][55][56][57][58]. In addition, LDHs possess beneficial properties, such as high surface area, high dispersity, high anionic drug loading ability and good biocompatibility [59,60] with controlled drug release [26,36,40,55,[61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…LDHs have been used as a carrier for various negatively charged bio-moieties, for instance siRNA [31,[41][42][43][44][45][46], antibodies [2], carbohydrates [47], amino acids [48], enzymes [49], antimicrobial drugs [50,51], anti-inflammatory drugs [52], and anticancer drugs [33,36,[53][54][55][56][57][58]. In addition, LDHs possess beneficial properties, such as high surface area, high dispersity, high anionic drug loading ability and good biocompatibility [59,60] with controlled drug release [26,36,40,55,[61][62][63][64][65][66]. LDHs are well known for their targeting ability [67][68][69] and easy particle functionalization [70].…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of LDH materials has been exploited to gain the benefits in a nano construct with multiple functions. This combination has shown to impart additional benefits such as targeting ability [29], controlled drug release [30], easy particle functionalization [31], improved biocompatibility [32] and enhanced photostability and contrast efficacy of imaging agents [33]. These properties make LDHs attractive for PDT applications and permit high loading of photosensitizers while the avid cellular uptake enables substantial intracellular accretion of photosensitizers for ideal PDT [34].…”
Section: Introductionmentioning
confidence: 99%